(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The article aims to discuss the potential of media images in art education, especially advertising images, based on the curricular guidelines of Brazil and Quebec, reflecting on the contributions and limitations found in these documents. First, the text discusses the importance of encouraging a sensitive and critical reading of the media images that circulate in students’ daily lives. Then, the Common National Curricular Base (BNCC) (Brazil, 2017), the current official document that guides Brazilian education, and the Quebec School Formation Program (PFEQ) (Québec, 2007) are examined, considering the relevance attributed to media images in the process of teaching visual arts. It is understood that it is essential that art education incorporates didactic and pedagogical practices of image reading that favor students’ perception, critical and creative reflection, allowing them to appropriate media images and understand them as agents of meaning production.